Lexical-Semantic Development in Bilingual Toddlers at 18 and 24 Months - De Anda, Stephanie; Friend, Margaret (Frontiers in Psychology, 2020)
An important question in early bilingual first language acquisition concerns the development of lexical-semantic associations within and across two languages. The present study investigates the earliest emergence of lexical-semantic priming at 18 and 24 months in Spanish-English bilinguals and its relation to vocabulary knowledge within and across languages. Results indicate a remarkably similar pattern of development between monolingual and bilingual children, such that lexical-semantic development emerges from 18 to 24 months of age. Further, measures of cross-language lexical-semantic associations (translation equivalents) are stronger predictors of children’s lexical-semantic processing skill than measures that capture lexical breadth only. This suggests that children make use of both languages when processing semantic information. Together these findings inform the understanding of the relation between lexical-semantic breadth and organization in the context of dual language learners in early development.